The Correlation between Administration of Alpha Lipoic Acid and Malondialdehyde Level on Traumatic Brain Injury Model Rat’s Brain - Nastiti Bekti Utami; Dini Agustina; Erfan Efendi (Faculty of Medicine, University of Jember, 2018)
Chronic traumatic encephalopathy (CTE) is a neurodegenerative disease caused by repetitive brain trauma that cancontinues to be dementia, alzheimer and parkinsonism. Traumatic brain injury increased free radicals in brain thatcaused oxidative stress and induced lipid peroxidation, neuron damage and producing MDA. The purpose is todetermine the correlation between administration of ALA and MDA level in rat’s brain model of traumatic braininjury and its effective dose. Rats are randomLy divided into 7 groups. Normal group without treatment, K(-) wasgiven NaCl 0,9% 1,5 mL, K(+) was given citicoline 6,75 mg, K1 was given ALA 1,0125 mg, K2 was given ALA 2,025mg, K3 was given ALA 4,05 mg, K4 was given ALA 8,1 mg and received 30 days traumatic brain injury treatment bydropped 245 g load on the rat’s head at 35 cm height. MDA level in brain were measured on the 31th day withMDA-TBA method by spectrofotometer. The averages of MDA levels were N 1,64 μg/mL; K(+) 2,09 μg/mL; K(-) 4,87μg/mL; K1 2,73 μg/mL; K2 2,68 μg/mL; K3 2,20 μg/mL and K4 2,02 μg/mL. Pearson’s analysis shows strong andsignificant negative correlation (r= -0,790) between administration of ALA and MDA level in rat’s brain model oftraumatic brain injury (p<0,05). The effective dose of ALA is 8,625 mg/150gBW.Keywords : Alpha lipoic acid, MDA, traumatic brain injury, CTE